Protective Actions of Acidic Hydrolysates of Polysaccharide Extracted From Mactra veneriformis Against Chemical-Induced Acute Liver Damage - Wang, Lingchong; Yang, Ying; Tan, Hor-Yue; Li, Sha; Feng, Yibin (Frontiers in Pharmacology, 2020)
The present study aimed to explore the hepatoprotective effects of acidic hydrolysates of polysaccharide extracted from the marine clam M. veneriformis (Ah-MVPS) against ethanol- and CCl4-induced liver damage. Moreover, we also seek to probe the mechanism associated with the liver protection effect of Ah-MVPS. A series of animal and cell experiments were executed to detect suitable serological and histological indicators in hepatic tissues. Ah-MVPS can significantly reduce liver damage by means of an increase in hepatocyte superoxidase dismutase and inhibition of leakages of alanine aminotransferase and aspartate transaminase, as well as through alleviation of malondialdehyde excalation. Ah-MVPS inhibited steatosis and water-like hepatic deterioration in histological examination. They can suppress membrane destruction in boundaries and the collapse of reticular scaffolds of injured mouse hepatocytes and can substantially reduce the inflammatory extent of liver tissue aroused by excessive intake of ethanol or CCl4. In cell assays, Ah-MVPS markedly elevated the viability of L-02 cells exposed to an intoxication of ethanol or H2O2. The beneficial effect of Ah-MVPS might arise, at least in part, because of the amelioration of peroxidation or oxidative stress. Taken together, our findings reveal that Ah-MVPS have potential for development as protective agents to attenuate acute liver injuries.